The Relationship between Social Media Literacy Skills and Academic Achievement of Generation Z University Students - Deden Purbaya (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study examines the relationship between social media literacy skills and academic achievement in Generation Z students using a quantitative correlational approach. The study's background is driven by significant shifts in communication patterns and information access influenced by the dominance of social media platforms, making the ability to sort, assess, and utilize digital information crucial for the learning process. The study sample involved 320 students from various faculties at a state university in Indonesia selected through stratified random sampling. Data collection was conducted through a structured questionnaire that measured dimensions of social media literacy skills including source evaluation skills, information credibility assessment, educational content production skills, and privacy management as well as GPA as an indicator of academic achievement. Construct validity was tested using confirmatory factor analysis and reliability was estimated using Cronbach's alpha coefficient. Data analysis used Pearson correlation and multiple linear regression to examine the strength and direction of the relationship between variables. The results showed a moderate positive correlation between overall social media literacy skills and academic achievement (r = 0.41, p < 0.01). From a specific dimension, source evaluation skills and educational content production skills significantly contributed to GPA variation, while privacy management showed no significant relationship. These findings indicate that strengthening social media literacy focused on information evaluation and content production can support the academic achievement of Generation Z students. Practical implications include recommendations for integrating social media literacy modules into curricula and training programs for lecturers and students. Study limitations and suggestions for further research are also discussed.